"I don't see myself as a 40-year-old on Facebook": medical students' dilemmas in developing professionalism with social media. Issue 2 (7th February 2019) - Curtis, Fiona; Gillen, Julia
Abstract: Students' development of professionalism is vital within medical education, while social media communications can blur professional and personal boundaries. In the UK advice for medical practitioners and students has been developed, advocating care in the projection of a professional identity online as offline. This study takes an academic literacies approach to a small-scale investigation of attitudes and practices of second-year medical students in a British university through a focus group and paired interview, recognising that issues of identity and power are multi-layered and complex. Use of social media focuses primarily on Facebook, where they had already begun to adapt their self-presentation. Depictions of alcohol use are a particular area of concern. The students' reflections demonstrate professionalism in respect of care for patient confidentiality and privacy. Yet they express an ambivalent sense of a future trajectory in which continuing social media use may appear simultaneously undesirable and yet vital. A finding of considerable concern is a reluctance to challenge inappropriate online behaviour despite policy guidelines. New generations growing up with social media raise challenges and opportunities for medical education that require greater attention and the development of participatory approaches to research, increasing understanding that in turn may be beneficial for policy-makers.